A Quality Management Strategy Based on an Internal Quality Assurance System to Improve the Quality of Teaching - Siti Zuliani; Mujahidin Mujahidin; Eldian Asriani (At Tadbir: Journal of Islamic Education Management is published by the Islamic Education Management Study Programme, IAI al Urwatul Wutsqo, Jombang, East Java, Indonesia., 2026)
Improving the quality of teaching at vocational secondary schools requires a quality management system capable of integrating the entire learning process. This study aims to analyse the implementation of the School-Based Quality Management System (SPMI) in improving the quality of teaching at SMKN Wonosalam, Jombang. The study employs a qualitative approach using a case study design. Data were collected through in-depth interviews, participatory observation and documentation, and were subsequently analysed using the interactive model developed by Miles, Huberman and Saldaña, comprising the stages of data condensation, data presentation and drawing conclusions. The research findings indicate that quality management strategies are implemented through quality control, academic supervision, periodic monitoring and evaluation, and continuous improvement within the SPMI framework. The implementation of these strategies still faces challenges in the form of teachers’ administrative discipline, the diversity of students’ prior abilities, and differences in the characteristics of each vocational programme. Improvements in the quality of teaching are achieved through strengthening teachers’ competencies via subject-specific teacher working groups (MGMP), learning communities (Kombel) and industry training; the transformation of learning towards project-based learning supported by digital technology; and the strengthening of the monitoring system and the creation of a conducive learning environment. This study confirms that the effectiveness of quality management in vocational schools depends not only on the application of the SPMI cycle, but also on the school’s ability to integrate quality assurance into daily teaching practices, thereby fostering a culture of quality that supports the continuous improvement of teaching quality